High repetition rate collisional soft X-ray lasers based on grazing incidence pumping - Shlyaptsev, Vyacheslav N., author; Keenan, R., author; Dunn, James, author; Rocca, Jorge J., author; Berrill, Mark, author; Allessi, David, author; Larotonda, Miguel A., author; Wang, Yong, author; Luther, Bradley M., author; IEEE, publisher (Colorado State University. Libraries, 2006)
We discuss the demonstration of gain-saturated high repetition rate table-top soft X-ray lasers producing microwatt average powers at wavelengths ranging from 13.9 to 33 nm. The results were obtained heating a precreated plasma with a picosecond optical laser pulse impinging at grazing incidence onto a precreated plasma. This pumping geometry increases the energy deposition efficiency of the pump beam into the gain region, making it possible to saturate soft X-ray lasers in this wavelength range with a short pulse pump energy of only 1 J at 800-nm wavelength. Results corresponding to 5-Hz repetition rate operation of gain-saturated 14.7-nm Ni-like Pd and 32.6-nm line Ne-like Ti lasers pumped by a table-top Ti:sapphire laser are reported. We also discuss results obtained using a 1 ⍵1054-nm prepulse and 2 ⍵527-nm short pulse from a Nd:glass pump laser. This work demonstrates the feasibility of producing compact high average power soft X-ray lasers for applications.
Keywords: soft X-ray laser; neon-like ions; nickel-like ions; grazing incidence pumping